The Effect of Cash Turnover Ratio, Total Asset Turnover, and Debt to Asset Ratio on Return on Assets - Siti Marfuah; Fanlia Prima Jaya; Diana; Muhammad Nurdin; Muhammad Darwis Meyandie Nasution (LifeSciFi, 2026)
This study is motivated by the importance of financial performance analysis in the automotive industry listed on the Indonesia Stock Exchange (IDX), particularly in assessing the effectiveness of asset management, liquidity, and capital structure on company profitability. This study aims to analyze the effect of Cash Turnover Ratio (CTR), Total Assets Turnover Ratio (TATO), and Debt to Asset Ratio (DAR) on the Return on Asset (ROA) of automotive companies listed on the Indonesia Stock Exchange in 2020-2024. The method used is a quantitative approach with multiple linear regression analysis. The sample consists of 9 automotive companies listed on the IDX over a five-year period (2020–2024), using financial statement data as the primary source. The results show that, partially, CTR and DAR have no significant effect on ROA, while TATO has a significant effect on ROA. Simultaneously, CTR, TATO, and DAR significantly affect ROA. The findings indicate that asset utilization efficiency is the key determinant of profitability in automotive companies. These results can serve as a reference for management in improving asset management efficiency and for investors in evaluating company performance.